The Role of Ferritin Levels on Vitamin D Status in Pregnant Women: An Observational Single Center Study at Hermina Hospital, Padang, Indonesia - Hidayat, Hedo; Efrida; Elfira Yusri (HM Publisher, 2024)
Background: Vitamin D deficiency during pregnancy is associated with poor pregnancy outcomes. Research shows a complex interaction between iron and vitamin D. Pregnant women are susceptible to iron deficiency due to increased iron requirements during pregnancy. Ferritin reflects body iron stores and may decrease before serum iron. This study aims to analyze the relationship between ferritin levels and vitamin D status in pregnant women. Methods: This retrospective comparative cross-sectional analytical observational study involved pregnant women in the 1st, 2nd, and 3rd trimesters who underwent antenatal care at Hermina Hospital Padang from February to August 2023. Vitamin D (25(OH)D3) and ferritin were measured using enzyme-linked fluorescence assay (ELFA). Univariate and bivariate analysis used the Chi-square and odds ratio (OR) tests, with a significance of p<0.05. Results: Of 163 pregnant women (mean age 30.4 years), median ferritin levels were 25.85 ng/mL and 25(OH)D3 15.5 ng/mL. Low ferritin was found in 63.80% of subjects and sufficient vitamin D in 31.90%, insufficiency in 33.74%, and deficiency in 34.36%. There was no correlation between low ferritin and vitamin D insufficiency (OR=2.04; 95% CI 0.94-4.42; p=0.700). However, there was a significant correlation between low ferritin and vitamin D deficiency (OR=6.59; 95% CI 2.68-16.18; p=0.000). Conclusion: Pregnant women with low ferritin have a 6.59 times higher risk of experiencing vitamin D deficiency.